Brasilian teenagers from an agricultural family school of Maranhão: From ideals/ought self to actual self - Judite Zamith Cruz; Marly Costa (INFAD, 2019)
After the installation of Field Schools in Brazil, it was in Maranhão that the Action Research was grounded. For this end, we analyzed mixed texts (Rose, 2005). We tried to understand school failure, using “techniques for making comparisons” (Strauss Corbin, 1990, pp. 77-81, pp. 84-91), between speeches, texts and drawings, in the class of 5th grade from the Agricultural Family School. How to face the imposition of a Life Project? The methodological analysis followed a training course in the field of “good character”. An “open coding” introduced future motivations and memories. The theoretical framework addressed two self-images: “ideal/ought self” (Higgins et al., 1994, p.276). In order to awaken our “theoretical sensitivity” (Strauss Corbin, 1990, pp. 41-47), the “analysis of words, phrases, paragraphs” was carried out; and the “shuttle” technique was used between phenomena. A “red flag” was placed by not asking certain questions to “not motivated” students. In the dimension “past path-future desire”, three codes were constructed: ideal self (future), change (past) and present loneliness. In the first one, the categories were ambitions and professions, with subcategories according to sex. The ambitious professions were never from the agricultural field. In the second code, the focus was on changing physical appearance, personality, friendships, dating and rejection, transition, admission to EFA, memorial days... In the third code, there was the forced removal of parents, their isolation and gender roles. No indiscipline and/or revolt against norms were detected. The script of boys in the brushcutting work is distinct different from girls’ action patterns. Allocation of resources, teacher training, particularly the incentive to success, is required when the student-teacher ratio is low and the agricultural school-family ratio (REFA) is effective. It is difficult to separate the REFA result from the placebo effect, which students benefit whenever adults get involved in a device they “believe” in.